2017
DOI: 10.1007/s10750-017-3210-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA (eDNA) detects the invasive crayfishes Orconectes rusticus and Pacifastacus leniusculus in large lakes of North America

Abstract: We report results of a study that made reciprocal comparisons of environmental DNA (eDNA) assays for two major invasive crayfishes between their disparate invasive ranges in North America. Specifically, we tested for range expansions of the signal crayfish Pacifastacus leniusculus (Dana, 1852) into the Laurentian Great Lakes region known to be invaded by the rusty crayfish Orconectes rusticus (Girard, 1852), as well as for the invasion of O. rusticus into large lakes of California and Nevada, US known to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 53 publications
8
62
0
Order By: Relevance
“…Furthermore, eDNA can be stored in sediments for months and possibly years, which may then get flushed periodically during spring releases (e.g., Turner et al 2015). eDNA has been successfully used in very large freshwater habitats like the Great Lakes of North America, but evidence suggests that target species DNA was not well mixed across such large expanses (e.g., Jerde et al 2013, Larson et al 2017. Relative to comparable eDNA sampling within reservoirs, eDNA sampling at downstream streamgages may result in a high proportion of negatives, even when the target species is present in the reservoir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, eDNA can be stored in sediments for months and possibly years, which may then get flushed periodically during spring releases (e.g., Turner et al 2015). eDNA has been successfully used in very large freshwater habitats like the Great Lakes of North America, but evidence suggests that target species DNA was not well mixed across such large expanses (e.g., Jerde et al 2013, Larson et al 2017. Relative to comparable eDNA sampling within reservoirs, eDNA sampling at downstream streamgages may result in a high proportion of negatives, even when the target species is present in the reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…If transport time is slow and water quality conditions are caustic to DNA (e.g., warm temperatures and high UV exposure; Pilliod et al 2014, Seymour et al 2018, then the target DNA may decay before it reaches a downstream streamgage. In these studies, positive eDNA detections were limited to <34 km and ≤4 km of previously observed localities for crayfish (Faxonius rusticus; Larson et al 2017) and Asian carp (Hypophthalmichthys spp. Reservoirs in the West, including those in this study, are also large.…”
Section: Discussionmentioning
confidence: 99%
“…In general, eDNA has performed well for representing occupancy of species (Dougherty et al., ; Pilliod et al., ; Smart et al., ), and some studies have found strong agreement between abundance or biomass of organisms and abundance of eDNA in the environment (Doi et al., ; Klobucar et al., ). Specific to crayfishes, studies have generally found eDNA to accurately represent occupancy of crayfishes, potentially with more sensitivity than some conventional methods, but eDNA has performed poorly in reflecting crayfish abundance (Agersnap et al., ; Cai et al., ; Dougherty et al., ; Larson et al., ). In some of these cases, the poor ability of eDNA to estimate abundance relative to conventional sampling methods could be related to weaknesses of the conventional methods themselves; for example, baited trapping of crayfishes has known biases and limitations that could fail to accurately reflect crayfish biomass (Larson & Olden, ; Stuecheli, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thermal flexibility has also been reported in crayfishes (Haubrock et al, 2019;Veselý, Buřič, & Kouba, 2015); for instance, Veselý et al (2015) reported from laboratory experi- (Larson et al, 2017) and P. clarkii (Tréguier et al, 2014). In addition, niche modelling cannot consider thermal flexibility of some species.…”
Section: Potential Distributions Under Current and Future Climate Smentioning
confidence: 99%